Investigation of the Necessity of Urodynamic Test in Patients with Urinary Stress Incontinence for TOT Surgery - Tahereh Poordast; Elham Askari; Fatemeh Sadat Najib; Shaghayegh Moradialamdarloo; Najmeh Naghizadeh (Shahrekord University of Medical Sciences, 2020)
Background and aims: Stress urinary incontinence is one of the most common diseases which can reduce the quality of life in women. Urodynamic test is a common method of diagnosis of this disease. This study is designed for investigating the necessity of urodynamic test in patients with urinary stress incontinency before transobturator tape (TOT) surgery. Urodynamic test before surgery can affect the quality of life in patients. Methods: This study was a randomized clinical trial. The sample size was 48 patients divided into two groups of 24 women in January 2018. Women with urinary incontinence complaints were randomly divided into two groups. For the first group, the urodynamic test was done. Both groups were evaluated one month and six months after TOT surgery based on the results of the I-QOL questionnaire. Results: The mean I-QOL score was 83.9±3.3 in questionnaire group and 81.6±4.6 in urodynamic group one month after surgery with no statistically significant (P=0.052) difference. The quality of life score after 6 months was 87.2±4 in the questionnaire group and 85.4±3 in the urodynamic group with no statistically significant differences with each other (P=0.084). Conclusion: In this study, the urodynamic test only had additional information related to lower urinary tract symptoms and it did not have effects on improving the outcome of the surgery. The test only imposes economic burden. Therefore, the urodynamic test is not required before surgery in patients with urinary stress incontinence